The Role of The Prosecutor’s Office in Asset Seizure - Sulistiyono, Adi; Isharyanto, Isharyanto; Purnama Adi , Fadhil (Ann Publisher, 2023)
The seizure of assets resulting from criminal acts will be easier for law enforcement officials to carry out if the Draft Law on Asset Forfeiture is passed. Assets that are seized are not only related to corruption crimes but also general crimes that carry a prison sentence of 4 years or more. The amount of assets seized is also at least IDR 100 million. This paper will explore the urgency of the Asset Forfeiture Bill in terms of the politics of legislation and then be limited to discussions on the direction of law enforcement that is considered responsive, especially regarding institutions that have authority in implementing the law. This paper is a type of doctrinal research that the data collection technique used is a literature technique, while the analysis in this study is after all legal materials are collected both from primary legal materials and secondary legal materials then clarified. Without strong watchdog institutions, impunity becomes the very foundation upon which systems of corruption are built. And if impunity is not demolished, all efforts to bring an end to corruption are in vain. Integrity, transparency, and the fight against corruption have to be part of the culture.